As cátedras Paulo Freire no Brasil: espaços de reinvenção do legado freireano - Matos, Ricardo Brasileiro (2024)
This master's thesis is part of the thematic area Paulo Freire thought in public education, from the Line of Knowledge and Educational Practices of the Postgraduate Program of the Faculty of Education at Universidade Federal de Uberlândia. The question that motivated this research: how are the Paulo Freire Chairs organized in Brazil? How do they work? What actions do they take? Based on this problematization, we defined the general objective: to investigate the forms of organization of the Paulo Freire Chairs in Brazil and the specific objective: to describe the location of the existing Chairs in Brazil; investigate the differences between the researched chairs; analyze the work and activities carried out by the Chairs; identify the praxis in the management of Chairs in Brazil and Freire's reinvented legacy. For this, qualitative/descriptive research was the methodological path chosen for understanding and analyzing the data collected. To collect data, we sent a questionnaire prepared from a Google Forms form. Of the fourteen Chairs in Brazil, nine of them were initially contacted and of this total, five responded to the questionnaire and participated in the research. From a documentary analysis, it was possible to identify the different ways in which the Chairs have been organized in the country, as well as the contributions they have made to the Freirean legacy. The analysis was carried out through three works: Paulo Freire: a biobibliography, organized by Moacir Gadotti (1996), Paulo Freire: a life story, by Ana Maria Araújo Freire (2006) and History of Paulo Freire's ideas and the current crisis of paradigms, written by Afonso Celso Scocuglia (2019), in addition to the book Education as Practice of Freedom by Paulo Freire. Based on the data analyzed, it can be stated that the Chairs seek to study Freirean thought and principles in an institutional space that breaks university discipline. Five categories of analysis were identified: praxis, inclusion, sustainability, dialogicity and politicality. It is concluded that the Paulo Freire Chairs contribute to the reinvention of his legacy, with teaching, research and extension actions in Institutions concerned with sharing and reinventing the Freireano legacy.